Communication and cultural inheritance through a traditional school in Dangiang Village, Garut - Perbawasari, Susie; Sjoraida, Diah Fatma; Anisa, Renata; Subekti, Priyo; Bakti, Iriana (Universitas Padjadjaran, 2023)
Background: Traditional medicine using herbal plants is one of the cultural assets of Indonesians. Belief in the efficacy of herbal plants as a definite treatment has been recognized for generations, especially among indigenous peoples. Purpose: This research aims to determine the role of a traditional school in bequeathing the culture of herbal medicine through health communication. Methods: This study employed a qualitative method. The data were collected using participatory observation, in-depth interviews, and guided group discussions. Results: The research results reveal six health communication methods to bequeath the culture of the use of herbal plants for health: 1) lecturing, 2) demonstrating, 3) hands-on practicing with assignments, 4) sharing, 5) role modeling, and 6) storytelling. The medical techniques of the indigenous people of Dangiang are categorized into three: 1) using the mind (medicine as communication media), 2) using herbal plants, and 3) using chemical drugs. The Dangiang community imposes special treatment to maintain public health, especially water use and waste disposal. Conclusion: Dangiang Traditional Village community is trying to preserve the traditional culture inherited from their ancestors, especially by using medicinal plants for health. Implications: This traditional school is expected to bring two final results: a) to bequeath traditional medicine culture, b) to preserve and maintain the local culture, and c) to inform the young generation about local customs and culture.